2010
DOI: 10.1177/0956797609359624
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Anxiety

Abstract: Anxiety modulates the functioning of attention. Although the existence of this relationship is clear, its nature is still poorly defined. Added are the facts that different types of anxiety--state or trait--may influence attention differently and that attention is not a unitary system. We studied the influence of such types of anxiety by means of a task that, using emotionally neutral information, assesses the efficiency of three attentional networks: orienting, alerting, and executive control. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
157
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(188 citation statements)
references
References 22 publications
17
157
5
1
Order By: Relevance
“…As WM load did not influence eye movements in this study, we tentatively suggest that executive control regulates these later processes, probably including appraisal, and does not so strongly regulate earlier processes such as orienting towards threat. Further support for this notion comes from the fact that eye movements to threat were associated with state rather than trait anxiety: evidence suggests that state anxiety is more closely associated with alerting and orienting, whereas trait anxiety is more closely associated with overall executive control deficits (Bishop et al, 2007;Pacheco-Unguetti, Acosta, Callejas, & Lupiáñez, 2010). Note that these eye movement results do not invalidate our interpretation of the RT data, because attention is able to operate independently from eye movements (e.g.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As WM load did not influence eye movements in this study, we tentatively suggest that executive control regulates these later processes, probably including appraisal, and does not so strongly regulate earlier processes such as orienting towards threat. Further support for this notion comes from the fact that eye movements to threat were associated with state rather than trait anxiety: evidence suggests that state anxiety is more closely associated with alerting and orienting, whereas trait anxiety is more closely associated with overall executive control deficits (Bishop et al, 2007;Pacheco-Unguetti, Acosta, Callejas, & Lupiáñez, 2010). Note that these eye movement results do not invalidate our interpretation of the RT data, because attention is able to operate independently from eye movements (e.g.…”
Section: Discussionmentioning
confidence: 71%
“…This is inconsistent with the dissociation between trait and state anxiety effects on RTs in our Study 2. Evidence supports the notion that trait and state anxiety may have differentiable effects on cognition (Pacheco-Unguetti et al, 2010); further research is required to fully investigate this difference with regard to both performance-based and eye movement-based biases.…”
Section: Discussionmentioning
confidence: 89%
“…However, there is a lack of empirical data concerning a difference between state and trait anxiety impact on cognitive processes. It has been recently argued that trait anxiety is related to deficiencies in the executive control attentional network, while state anxiety is associated with hyperactivity of the alerting and orienting networks (Pacheco-Unguetti, Acosta, Callejas, & Lupianez, 2010). Consistent with ACT, neuroimaging studies demonstrated that high-anxious individuals had to invest more cognitive (compensatory) efforts in task performance which manifested itself as an increased task-related activation of the prefrontal cortex (PFC) (Ansari & Derakshan, 2011;Basten, Stelzel, & Fiebach, 2011;Eisenberger, Lieberman, & Satpute, 2005).…”
mentioning
confidence: 62%
“…Pacheco-Unguetti et al [7] demonstrates that high trait-anxious individuals exhibit difficulty responding to a target arrow flanked with perceptually competing distractor arrows relative to those low in trait anxiety. Similarly, high trait-sanxiou individuals have been shown difficulty performing anti-saccade tasks, in which participants are required to execute a saccade (horizontal eye movement) toward a target stimulus located in the opposite direction of a perceptually salient flashed stimulus [8] [9].…”
Section: Introductionmentioning
confidence: 99%